SOVIET PHILOSOPHICAL UNDERGROUND: PRACTICES OF SURVIVING - Natalia I. Kuznetsova (Высшее образование в России)
It is commonly recognized that after the departure of the infamous "philosophers' steamer" in 1922, Russia inexorably declined into an epoch of "philosophical silence" due to the dictatorship of the Marxist-Leninist ideology, which forbade any kind of a diverging worldview. It is assumed that no original or significant ideas could have been expressed within that period of history. The author disputes the general thesis that there was no philosophy within the Soviet Russia. In 1960-1970s there appeared philosophical circles, informal leaders, the original research programmes and theoretical conceptions, and the most important - the genuine schools of philosophical thinking. The geography of the well-known "home seminars" is rather diverse: Moscow, Rostov-on-Don, Novosibirsk, Minsk. These groups and unions were not institutionalized, and their members had no social privileges. It can be said that there appeared an original sociocultural phenomenon - soviet philosophical "underground". The paper analyzes the motives and behavioral patterns of the youth involved in such activity in such format. Special attention is paid to the activities of the Moscow Methodological Circle created by Georgy Shchedrovitsky. Shchedrovitsky's seminars were aimed at reflection the means of thinking and embodied the idea that thinking is a collective effect.